Brillouin frequency shift measurement by zero-crossing point search in virtually synthesized spectra of Brillouin gain and loss - Hayato Nonogaki; Daichi Sei; Mohd Saiful Dzulkefly Zan; Yosuke Tanaka (Applied Physics Express, 2024)
We demonstrate a method for fast and precise Brillouin frequency shift measurement based on searching for the zero-crossing point of a virtually composed spectrum of Brillouin gain and loss obtained by a dual-frequency probe beam. Simulations and experiments show that searching for the zero-crossing point of a virtually synthesized Brillouin gain spectrum can be easily done without a large error compared with peak search of the Brillouin gain spectrum in the conventional method.